2014
DOI: 10.1038/ijo.2014.214
|View full text |Cite
|
Sign up to set email alerts
|

Fasting for weight loss: an effective strategy or latest dieting trend?

Abstract: With the increasing obesity epidemic comes the search for effective dietary approaches for calorie restriction and weight loss. Here I examine whether fasting is the latest 'fad diet' as portrayed in popular media and discuss whether it is a safe and effective approach or whether it is an idiosyncratic diet trend that promotes short-term weight loss, with no concern for long-term weight maintenance. Fasting has long been used under historical and experimental conditions and has recently been popularised by 'in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 55 publications
1
93
0
7
Order By: Relevance
“…There are different forms of fasting, including intermittent fasting and periodic fasting lasting several days or longer (two or more weeks) [9]. Rather than reducing daily total caloric intake, intermittent fasting (IMF) has received attention as a possible approach for long-term weight loss [10, 13]. However, there are some controversies regarding the effects of fasting and refeeding on weight regain [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…There are different forms of fasting, including intermittent fasting and periodic fasting lasting several days or longer (two or more weeks) [9]. Rather than reducing daily total caloric intake, intermittent fasting (IMF) has received attention as a possible approach for long-term weight loss [10, 13]. However, there are some controversies regarding the effects of fasting and refeeding on weight regain [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Fasting is also widely used and recommended for rapid weight loss [13] and for disease prevention and treatment [2]. It is well known that long-term intermittent and periodic fasting promotes health and reduces the risk of many chronic diseases, such as cancer, neurodegenerative diseases, metabolic syndrome, hypertension, and inflammation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Increased health span and longevity in rodents has been linked since many years to intermittent fasting that is a protracted time without ingestion of calories and nutrients for at least 20 hours on alternate days (Carlson and Hoelzel, 1946;Martin et al, 2006;Mattson and Wan, 2005). Studies carried out in humans demonstrated that several weeks of an alternate day fasting (ADF) reduce body weight and fat mass and improve clinical health markers thus restraining metabolic dysfunctions likely leading to prolonged life span (Johnstone, 2015;Seimon et al, 2015;Tinsley and La Bounty, 2015). However, only a few human studies have 4 tested the effects of ADF on body weight and pro-longevity parameters in non-obese subjects.…”
Section: Introductionmentioning
confidence: 98%